THE RHETORICAL TRIANGLE REALIZATIONS ON TOURISM PROMOTION VLOG IN RECREATIONAL TOURISM - Afore T Harefa; Septika N Gulo; Mega R Zebua; Rizka H Hia (Fakultas Hukum dan Sosial Humaniora Universitas Flores, 2026)
This study aims to analyze how the rhetorical elements of credibility, emotion, and logic are realized in tourism promotion vlogs and how their integration contributes to persuasive effectiveness in recreational tourism promotion. The research employed a qualitative approach with design focusing on tourism promotion vlogs about Kamadu Beach. The participants consisted of 24 respondents who had no prior familiarity with the destination. Data were collected through the selection of tourism vlogs from digital platforms and interviews guided by a questionnaire to capture respondents’ perceptions. The data were analyzed using a rhetorical triangle framework by examining narrative and visual elements to identify persuasive strategies. The results show that emotional appeal is the most dominant element in tourism promotion vlogs and plays a significant role in attracting audience attention and increasing engagement. However, logical information supports rational decision-making, while credibility strengthens audience trust in the content. The study concludes that effective tourism promotion vlogs require a balanced integration of emotional appeal, logical information, and credible presentation to enhance persuasive impact and encourage actual tourist visits. The findings imply that content creators and tourism promoters should strategically combine these rhetorical elements to achieve more effective digital tourism promotion.